Comparison the effects of animal fat (ghee) with that of vegetable fat (dalda) in respect to hemato-biochemical parameters in mice - Rahman, Md Saidur; Hasan, Md Mehedi; Kabir, Md Ehsanul; Sultana, Nahid Nawrin; Bhuiyan, Md Eliusur Rahman; Ahmad, Nazim (Asian Journal of Medical and Biological Research, 2018)
The experiment was conducted to compare the effects of animal fat (ghee) and vegetable fat (dalda) in respect to hemato-biochemical changes in mice. A total of twenty one, 45 days old (Swiss Albino) mice were randomly divided into three equal experimental groups as A, B and C (n=7). Group A was considered as control and fed only broiler pellet, group B was fed broiler pellet with ghee (25 gm/1000 gm feed) and group C was fed broiler pellet with dalda (25 gm/1000 gm feed) respectively. At day 40, all mice were sacrificed to collect blood for hematological parameters where blood profile was analyzed by biochemical tests. Total erythrocyte counts were significantly (p<0.05) higher in ghee and dalda supplemented mice (B: 8.99±.34 million/cu. mm. and C: 8.27±.43 million/cu.mm.) compared to control group (A: 7.49±.22 million/cu.mm.). The significantly (P<0.05) higher hemoglobin concentration was recorded in ghee supplemented group B (9.02±.18 gm/dl) than other groups and control group A showed lowest value (7.59±.52 gm/dl). In Blood profile analysis, serum cholesterol and HDL value were higher in ghee and dalda supplemented group than control group. On the other hand triglyceride value was significantly (P<0.05) lower in control group (A: 44±4.58 mg/dl) than ghee and dalda supplemented group (B: 80.33±2.51 mg/dl, C: 71.2±4.26 mg/dl). The study suggests that ghee and dalda supplementation with regular diet would be able to significantly increase cholesterol and triglyceride in mice. Asian J. Med. Biol. Res. June 2018, 4(2): 222-226